Golden memory lagu manca 90-1n vol.1 - HASAN, Andre (MedPress, 2010)
Buku ini berisi lagu: November Rain, Sweet Child O'Mine, Don't Cry, Rocket Queen, Mr Brownstone, Wild World, Green Tinted Sixties Mind, Nothing Else Matters, Master of Puppets, Never Say Goodbye, Life A Life Time, Here For You, Zombie, Age of Innocence, Iron Maiden, Avant Garden, Big Ten Inch Record, Can I Play Madness, About A Girl, Big Long Now, Breed, Come As You Are, Floyd The Barber, A Letter to Elise, New Hope.